Revisão taxonômica das espécies do gênero Hemiloricaria Bleeker, 1862 (Siluriformes, Loricariidae) da bacia do rio Paraguai. - Vera Alcaraz, Héctor Samuel (2008)
The Hemiloricaria species from the Paraguay River basin were revised and three species were found to be valid and one new is described. The following species and its distributional range were verified: H. cacerensis, Paraguay River basin in Brazil and Paraguay and Guaporé River in Brazil; H. lanceolata, Paraguay River basin in Brazil and Paraguay, Guaporé, Ji-paraná, Purus, Solimões and Araguaia River in Brazil, and Marañón and Madre de Dios River in Perú; H. parva, Paraguay River basin in Brazil and Paraguay, Paraná River in Argentina and Uruguay River in Brazil; and a new species from Cuiabá River in Brazil. Loricaria hoehnei is considered synonym of H. lanceolata and H. aurata synonym of H. cacerensis. Other species cited to the basin and the last arrangement of genera and species proposed by Isbrücker are discussed.